Consequences of Avian Flu for Growth and Poverty: A CGE Analysis for Kenya - Thurlow, James (Wiley, 2011)
Like many African countries, Kenya is vulnerable to avian flu given its position along migratory bird routes and proximity to other high risk countries. This raises concern about the effect of an outbreak on rural livelihoods. We use a dynamic computable general equilibrium model of Kenya to simulate outbreaks of different severities, durations and geographic spreads. Results indicate that even a severe outbreak does not greatly reduce economic growth. It does, however, have larger implications for poverty, since poultry is an income source for many poor farmers and a major food item in poor consumers' baskets. Reducing an outbreak's duration and spatial transmission substantially reduces economic losses, although losses still occur when poultry demand falls, even without a confirmed outbreak. Continued monitoring of poultry production and trade is therefore needed, even if an outbreak has not yet occurred. Efforts to enhance government capacity to respond rapidly to infections and improve farmers' and consumers' awareness of avian flu are also needed.